A SURVEY OF ADVERSE EVENTS FOLLOWING IMMUNIZATION OF COVID-19 IN HEALTH-CARE WORKERS AT TERTIARY CARE HOSPITAL IN SOUTH GUJARAT REGION - CHAUDHARI ARCHANABAHEN G; PATEL BRIJALKUMAR S; TANDEL KIRTIDA R (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to evaluate adverse events following immunization (AEFI) among the health-care workers (HCWs) who received both doses of the COVID-19 vaccine either COVISHIELD or COVAXIN. Methods: A questionnaire-based retrospective cross-sectional survey was carried out at the tertiary care teaching hospital of South Gujarat after getting approval from the Institutional Human Ethics Committee. A total of 542 HCWs who received two doses of vaccine were enrolled. Vaccine-related adverse effects and association of AEFI with demographic variables were determined. Results: Fever, pain at the injection site, and body aches were the common adverse events reported by the participants following both doses of COVISHIELD and COVAXIN. Most of the AEFIs were reported within 6–12 h of vaccination after the 1st and 2nd doses. We found no association of AEFI with comorbidity and previous COVID-19 infection. A significant association of AEFI was found with gender, age groups, and occupation (p<0.05). Conclusion: Most of the adverse events were non-serious and reported within 6–12 h of vaccination. Only few adverse events were reported after 24 h of vaccination and no serious AEFI was reported. Younger age groups, females, and HCWs are at higher risk of AEFI. Precaution needs to be taken while vaccinating these individuals.